Perancangan dan Implementasi Pembangkit Listrik Tenaga Mikrohidro (PLTMH) untuk Mendukung Ketersediaan Energi Berkelanjutan di Kampung 17, Desa Batulawang, Jawa Barat - Muhammad Zaidan Taftazani; Surya Chandra Kusuma; Benedictus Dimas Cahyo Priastono; Tsabit Arasyid; Firman Alfarisi; Sigit Hermawan; Marsya Royani Jannah; Muhammad Ridwan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Micro-Hydro Power Plant (MHPP) is a renewable energy solution suitable for remote rural areas with river flow availability. This study was carried out in Kampung 17, Batulawang Village, West Java, through the Community Service Program of HMM ITPLN, by designing and implementing a simplified MHPP system. The analysis indicates a hydraulic power potential of 1.511 kW with an effective head of 3.08 m and a discharge of 0.005 m³/s. Of this potential, the maximum utilized power reached 1.108 kW, equivalent to 73.32% of hydraulic energy utilization. The system is capable of producing approximately 26.6 kWh per day or around 798 kWh per month, matching the total demand of 12 households and one mosque in Kampung 17. If this demand were supplied by the national grid (PLN) under the R-1/TR 1300 VA category at Rp1,444.70 per kWh, the monthly cost would amount to approximately Rp1,152,870. Hence, the MHPP enables annual savings of around Rp13.8 million while ensuring local energy independence